Trade policy in retrospect. The great recession and the determinants of tariff and antidumping restrictions in Argentina, Brazil and Mexico - Jacobo, Alejandro D. (2019)
Fil: Jacobo, Alejandro D. Universidad Nacional de Córdoba. Facultad de Ciencias Económicas. Instituto de Economía y Finanzas; Argentina.